Another Type of Fuzzy Inner Product Space - Sabri , Raghad I.; Ahmed, Buthainah A. A. (Iraqi Journal of Science, 2023)
In this paper, we generalize the definition of fuzzy inner product space that is introduced by Lorena Popa and Lavinia Sida on a complex linear space. Certain properties of the generalized fuzzy inner product function are shown. Furthermore, we prove that this fuzzy inner product produces a Nadaban-Dzitac fuzzy norm. Finally, the concept of orthogonality is given and some of its properties are proven.